Evidence‐Based Interventions for Depressed Mothers and Their Young Children. Issue 2 (3rd February 2017) - Goodman, Sherryl H.; Garber, Judy
Abstract : Depression in mothers is a significant risk factor for the development of maladjustment in children. This article focuses on modifiable risk processes linking depression in mothers and adaptation in their young children (i.e., infancy through preschool age). First, the authors present evidence of the efficacy of interventions for reducing the primary source of risk: maternal depression. Second, they describe a central mechanism—parenting behaviors—underlying the relation between maternal depression and children's adjustment. Third, the authors recommend two different integrated interventions that successfully treat mothers' depression and enhance parenting skills with infants and young children. Finally, the authors note the possible need for supplementary interventions to address severity and comorbidity of mothers' depression, barriers to engaging in treatment, and the sustainability of program benefits. Abstract : The title for this Special Section isDevelopmental Research and Translational Science: Evidence‐Based Interventions for At‐Risk Youth and Families edited by Suniya S. Luthar and Nancy Eisenberg